Bluebeard`s Castle: vocal score - Bartók, Béla (Dover opera and choral scores, 2001)
The first vocal work and the only opera written by Béla Bartók (1881-1945), Bluebeard´s Castle is considered the greatest Hungarian opera. Thought it is concentrated into a singlo act and has only two characters, it burns with a fully operatic intensity - "a musical volcano." as Zoltán Koálu called it, that erups for sixty minutes of compressed tragedy".